Vivax malaria in a blood donor in Spain, relapse or a new infection in a malaria non‐endemic country?. Issue 2 (28th October 2015) - Rubio, J. M.; Jiménez del Bianco, A. I.; Cervera‐Alonso, Y.; Fernandez‐Garcia, M. D.; Lanza, M.; Ta Tang, T. H.; Sevil Puras, F.; Blanco, L.
Abstract : Malaria is a vectorborne disease caused by protozoan of the genus Plasmodium, which can also be transmitted by the transfusion of infected red blood cells. One year after return from a travel to Honduras, a Spanish traveller developed vivax malaria. Prior to the onset of symptoms, the donor made a donation that tested non‐reactive using an immunological test for malaria. Samples from the donor taken before donation and tested by serological and molecular methods were negative but positive at the time of hospital admission. The possible sources of the donors' infection, imported versus locally acquired, are discussed.